2018
DOI: 10.1155/2018/5727165
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Bilateral Sacrospinous Fixation after Second Recurrence of Vaginal Vault Prolapse: Efficacy and Impact on Quality of Life and Sexuality

Abstract: Objective Our aim was to study the efficacy of transvaginal bilateral sacrospinous fixation (TBSF) and its impact on quality of life (QoL) and sexual functions in women affected by second recurrences of vaginal vault prolapse (VVP). Materials and Methods We performed a prospective observational study on 20 sexually active patients affected by second recurrence of VVP, previously treated with monolateral sacrospinous fixation. TBSF was performed in all the patients. They had been evaluated before the surgery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…20 In patients with pelvic floor dysfunction, surgery is solely performed for resolution of the prolapse, while it should be additionally considered to improve the outcomes of sexual function and QoL. 21,22 In the literature, there are very few studies on sexuality and QoL in patients who underwent bilateral SSLF. In this study, we assessed the clinical effectiveness of the bilateral SSLF technique on 26 sexually active women affected by POP.…”
Section: Discussionmentioning
confidence: 99%
“…20 In patients with pelvic floor dysfunction, surgery is solely performed for resolution of the prolapse, while it should be additionally considered to improve the outcomes of sexual function and QoL. 21,22 In the literature, there are very few studies on sexuality and QoL in patients who underwent bilateral SSLF. In this study, we assessed the clinical effectiveness of the bilateral SSLF technique on 26 sexually active women affected by POP.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still an insufficient number of trials on the impact of urogynaecological surgery on sexual function. Recent studies have reported a considerable improvement of QoL and sexual function after cystocele and vaginal fault prolapse correction [60,61]. It is noteworthy that SUI and POP surgery not only affect the pelvic floor but also the whole physiological well-being of a woman, including her sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the cases of recurrent POP, vaginal vault prolapse was the most difficult to manage. Studies have provided strategies for prevention 24 and novel methods of treatment 25 . All techniques have been suggested to be effective, but a comparison of the techniques is difficult because of heterogenicity 26 .…”
Section: Discussionmentioning
confidence: 99%